Design of Academic Information System at Bintang Harapan Preschool - Saripa; Ariansyah; Jepriyandi (Yayasan Kita Menulis, 2026)
PAUD Bintang Harapan is an early childhood education located in Talang Batu Village, Rambang Kapak Tengah District, Prabumulih City, South Sumatra Province. Currently, PAUD Bintang Harapan in storing academic data is still in the form of archives, both student attendance, report card filling and tuition payment reports, so it is difficult to search for data. Therefore, the author tries to create a website-based academic information system using PHP and MySQL and UML assistance in designing the system created. This design uses the Extreme programming method, so it can be concluded that this system is feasible if the academic information system is implemented at PAUD Bintang Harapan.